Macroeconomics and the Environment. (International Monetary Fund, 1996)
Microeconomic policies, dealing with individual industries and economic sectors, have traditionally addressed environmental concerns, but increasingly the environment is being viewed in terms of the macro economy. To improve its understanding of the interrelationship between macroeconomics and the environment, the IMF held a seminar in May 1995 at which recognized experts from academic and research institutions, nongovernmental organizations, and staff from the World Bank and the IMF shared their views on how macroeconomic policies affect the environment and how environmental policies affect the macro economy. The present volume, edited by Ved P. Gandhi, contains the papers and proceedings of this seminar.